2018
DOI: 10.1038/s41598-018-32511-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Prediction of Hot Spots at Protein-Protein Interfaces Using Extreme Gradient Boosting

Abstract: Identification of hot spots, a small portion of protein-protein interface residues that contribute the majority of the binding free energy, can provide crucial information for understanding the function of proteins and studying their interactions. Based on our previous method (PredHS), we propose a new computational approach, PredHS2, that can further improve the accuracy of predicting hot spots at protein-protein interfaces. Firstly we build a new training dataset of 313 alanine-mutated interface residues ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 68 publications
1
49
0
Order By: Relevance
“…In this work, we developed a deep learning framework called 4mcDeep-CBI to identify the 4mC sites. Deep learning related methods are widely used in hot spots prediction of proteinprotein interfaces Wang et al, 2018;Deng et al, 2019;Liu et al, 2019), but we have not found any work with deep learning in 4mC sites prediction, and all previous studies have used SVM machine learning methods. This work is the first study of 4mC sites using deep learning.…”
Section: Introductionmentioning
confidence: 91%
“…In this work, we developed a deep learning framework called 4mcDeep-CBI to identify the 4mC sites. Deep learning related methods are widely used in hot spots prediction of proteinprotein interfaces Wang et al, 2018;Deng et al, 2019;Liu et al, 2019), but we have not found any work with deep learning in 4mC sites prediction, and all previous studies have used SVM machine learning methods. This work is the first study of 4mC sites using deep learning.…”
Section: Introductionmentioning
confidence: 91%
“…XGBoost is widely used by data scientists in multiple applications and has provided advanced results [58,59]. The training set after feature extraction and SMOTE…”
Section: Extreme Gradient Boosting Algorithmmentioning
confidence: 99%
“…HaoWang, ChuyaoLiu & LeiDeng et.al [5] applied XGBoost and built a model called PredHS2 for detection of hot spots. Hotspots tiny segments of protein-protein interface residues contributing majority of the binding free energy.…”
Section: Related Workmentioning
confidence: 99%